Flux dependence of helium retention in clean W(1 1 0): Experimental evidence for He self-trapping. (March 2023) - Dunand, A.; Minissale, M.; Angot, T.; Bisson, R.
Highlights: Clean W(1 1 0) was used to evidence the self-trapping of He in the W bulk at 300 K. 130 eV He + ions were implanted in W at a constant fluence of 2.0 × 10 21 He + m −2. Only if the He ion flux exceeds 0.7 × 10 17 He + m -2 s −1, we observed He desorption peaks. He desorption at 950 K and 1700 K are consistent with self-trapped Hen V clusters. At 5.0 × 10 17 He + m -2 s −1 new desorption peaks are consistent with trap-mutated Hen Vm>1. Abstract: Helium (He) retention in tungsten (W) is a concern in fusion reactors since it could be detrimental to plasma facing components performance and influence the fusion fuel balance. He being not soluble in W, it tends to agglomerate on preexisting defects (vacancy, grain boundary), but it could in theory also self-trap (be immobilized on a non-preexisting vacancy) through the emission of a vacancy/self-interstitial W pair in the vicinity of a Hen interstitial cluster. In the present study, we prepared a pure single crystal W(1 1 0) sample with a clean surface in order to evidence the self-trapping of He in the W bulk at a sample temperature of 300 K and for a constant fluence of 2.0 × 10 21 He + .m −2 . At a He + kinetic energy of 130 eV and a flux of 0.3 × 10 17 He + .m −2 .s −1, we only observed a small He desorption peak below 600 K. Rising the ion flux to 0.7 × 10 17 He + .m −2 .s −1, we observed the sudden appearance of two desorption peaks at 950 K and 1700 K. For the highest flux studied in this work, 5.0 × 10 17 He + .m −2 .s −1, an additional desorption peak at 1800 K and a desorption shoulder at 1900 K are observed. The temperature position of these He desorption peaks are consistent with the density functional theory literature and points to the occurrence of self-trapping once the 0.7 × 10 17 He + .m −2 .s −1 flux is attained at 300 K and to the possible realization of trap-mutation for the flux of 5.0 × 10 17 He + .m −2 .s −1 . The present set of results should be used to constrain the development of He retention and He bubbles growth models based on ab initio quantities.